2022
DOI: 10.1002/csr.2358
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable service ecosystems from the transformative value perspective: A study in tourism destinations

Abstract: The aim of this study is to examine the relationship between sustainability with customer satisfaction and service experience in service ecosystems, by analyzing the moderated role of business models. A model with four variables is proposed, whereby customer satisfaction is the dependent variable, perceived sustainability of the service ecosystem is the explanatory variable, service experience is the mediator variable, and business models is the moderator variable. The model is applied in a survey of tourists.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 70 publications
(150 reference statements)
2
8
0
Order By: Relevance
“…Moreover, the ordinary or extraordinary nature of customer–actor dyadic experiences is what determines the generation of service experience and MCE at the ecosystem level. All the customer’s dyadic interactions in the network can generate ordinary and extraordinary experiences, but the latter have more capacity to impact MCE at the aggregate level (Moliner et al , 2023; Lee, 2023). In contrast, ordinary dyadic experiences are the main generators of the service ecosystem experience at the aggregate level.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the ordinary or extraordinary nature of customer–actor dyadic experiences is what determines the generation of service experience and MCE at the ecosystem level. All the customer’s dyadic interactions in the network can generate ordinary and extraordinary experiences, but the latter have more capacity to impact MCE at the aggregate level (Moliner et al , 2023; Lee, 2023). In contrast, ordinary dyadic experiences are the main generators of the service ecosystem experience at the aggregate level.…”
Section: Resultsmentioning
confidence: 99%
“…This paper focuses on the main outcome of value co-creation: customer experience. The literature about customer experience differentiates between service experience and memorable customer experience (MCE), because the generation of memorable experiences has become a priority for services (Moliner et al , 2023). S-D logic postulates that different service providers create their own experiences but also contribute to generating ecosystem aggregate experience.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Russell-Bennett et al (2020) found that individuals may forgo their well-being for more considerable community benefits. According to Blocker and Barrios (2015) and Moliner‐Tena et al (2022), TSR deals with bringing positive change to individual and collective well-being (Galeone and Sebastiani, 2021). More recently, Dodds et al (2022) found that service organizations have the potential to make a positive impact on the well-being of individuals, businesses and society.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Recently, ref. [21] showed the impact of overall transformative value and perceived sustainability on service experience and customer satisfaction, using an ecosystem approach. Theoretically, sustainable consumption does not provide individual or private benefits, but it contributes to the collective good.…”
Section: Sustainable Marketingmentioning
confidence: 99%